2003
DOI: 10.1242/dev.00589
|View full text |Cite
|
Sign up to set email alerts
|

Tracking mesoderm induction and its specification to the hemangioblast during embryonic stem cell differentiation

Abstract: The hematopoietic and endothelial lineages derive from mesoderm and are thought to develop through the maturation of a common progenitor, the hemangioblast. To investigate the developmental processes that regulate mesoderm induction and specification to the hemangioblast, we generated an embryonic stem cell line with the green fluorescent protein (GFP) targeted to the mesodermal gene, brachyury. After the in vitro differentiation of these embryonic stem cells to embryoid bodies, developing mesodermal progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
534
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 462 publications
(576 citation statements)
references
References 52 publications
39
534
2
1
Order By: Relevance
“…We observed mRNA within 2-3 days for nestin (an early neural ectoderm marker) and brachyury (Brachy, an early mesoderm marker), whereas β-H1 globin (β-globin, a mesoderm marker) and α-fetoprotein (α-FP, an endoderm marker) mRNAs accumulated later (days 5-6). These patterns of expression are as previously reported for multilineage differentiation following LIF withdrawal [8,9,32,[38][39][40][41].…”
Section: Progesterone Receptor Gene Is Expressed Early During Differesupporting
confidence: 87%
“…We observed mRNA within 2-3 days for nestin (an early neural ectoderm marker) and brachyury (Brachy, an early mesoderm marker), whereas β-H1 globin (β-globin, a mesoderm marker) and α-fetoprotein (α-FP, an endoderm marker) mRNAs accumulated later (days 5-6). These patterns of expression are as previously reported for multilineage differentiation following LIF withdrawal [8,9,32,[38][39][40][41].…”
Section: Progesterone Receptor Gene Is Expressed Early During Differesupporting
confidence: 87%
“…Using an ES-cell line with the GFP cDNA targeted to the brachyury locus [43], we monitored early mesoderm development in differentiating cells by flow cytometry. Consistent with the described pattern of brachyury expression [43], GFP þ cells were detected between days 2 and 5 of differentiation in high glucose, with the greatest number of GFP þ cells occurring at days 3 and 4 ( Fig. 6A, 6B).…”
Section: Resultsmentioning
confidence: 99%
“…We found that different lines could be distinguished by the expression of primitive streak or mesendoderm-associated genes. The Brachyury gene is frequently used as a marker to track early cellular differentiation into the mesodermal lineage in vitro [18,19]. However, the very early (E5.5) pregastrulation epiblast is negative for Brachyury expression.…”
Section: Discussionmentioning
confidence: 99%